Hours Inequality - Daniele Checchi; Cecilia García-Pe\~nalosa; Lara Vivian (Center for Economic Studies and ifo Institute (CESifo), 2022)
The vast literature on earnings inequality has so far largely ignored the role played by hours of work. This paper argues that in order to understand earnings dispersion we need to consider not only the dispersion of hourly wages but also inequality in hours worked as well as the correlation between the two. We use data for the US, the UK, France, and Germany over the period 1991-2016 to examine the evolution of inequality in hours worked and of the correlation between individual hours and wages, assessing their contribution to recent trends in earnings inequality. We find that, other than in the US, hours inequality is an important force, and that it has increased over the period under analysis. The elasticity of hours with respect to wages has also played a key role, notably in the two continental economies. This elasticity used to be negative, thus tending to reduce inequality as those with lower hourly wages worked longer hours, but has increased over the past decades, becoming nil or positive, and hence eroding an important equalizing force. The paper examines which are the potential factors behind the change in the elasticity, notably the role of trade and labour market institutions.
Keywords: D31; J22; 330; earnings inequality; working hours; hours elasticity